UJI BEBERAPA VARIETAS TANAMAN PADI (Oryza sativa. L.) TERHADAP HAMA KEONG MAS (Pomaceae canaliculata Lamarck) (Mollusca; Ampulariidae) - Rudi Tomson Hutasoit (UNIVERSITAS LABUHANBATU, 2019)
Research about test of several varieties of rice plant (Oryza sativa L.) against pest snail (Pomaceae canaliculata Lamarck) (Mollusks; Ampullariidae) has been completed on the grounds of rice farmers in the Village of Limau Manis Subdistrict Pauh Padang of West Sumatera from December 2011 until May 2012. The aim of this research is to get varieties are resistant to pest snail. This study use Random Design Group (RAK) with eight and three treatment groups. Its treatment is the most common varieties planted in West Sumatera that is IR 66, Cisokan, IR 42, Kuriek Kusuik, Batang Piaman, Anak Daro, Caredek Merah, and Junjuang. Experimental units of rice plant field with the size of the map 1 x 1 m that contains 25 clump rice crops and given six tail snail in piloting. The parameter is the percentage of attacks observed snail, snail intensity of attack and production. Data analyzed by fingerprint variety and continued with Duncan’s New Multipele Range Test (DNMRT) on standard 5%. The result showed that all varieties are tested there is no that is resistant to pest snail attacks, but varieties Junjuang and Kuriek kusuik have more resisting power than with other varieties that are tested. Kata Kunci: varietas padi, Oryza sativa, Pomaceae canaliculata